Scaevola plumieri Inkberry: FPS539/FP539, 9/2007 - Gilman, Edward (EDIS, 2018)
The publication discusses Scaevola plumieri (Inkberry), a native shrub of Florida, known for its dense, low-growing habit and salt tolerance. It thrives in coastal areas and helps stabilize sand dunes. This plant features thick, glossy leaves and small, white, fan-shaped flowers. It is drought and salt-tolerant, making it ideal for coastal landscaping. Inkberry can be propagated from seeds or rooted stems and is primarily used as ground cover or in reclamation projects. The plant is not invasive and has minimal pest concerns. a. Original publication date October, 1999.